2021
DOI: 10.3389/fcimb.2021.643326
|View full text |Cite
|
Sign up to set email alerts
|

Virus-Induced Changes of the Respiratory Tract Environment Promote Secondary Infections With Streptococcus pneumoniae

Abstract: Secondary bacterial infections enhance the disease burden of influenza infections substantially. Streptococcus pneumoniae (the pneumococcus) plays a major role in the synergism between bacterial and viral pathogens, which is based on complex interactions between the pathogen and the host immune response. Here, we discuss mechanisms that drive the pathogenesis of a secondary pneumococcal infection after an influenza infection with a focus on how pneumococci senses and adapts to the influenza-modified environmen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
47
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 60 publications
(52 citation statements)
references
References 176 publications
(233 reference statements)
1
47
0
Order By: Relevance
“… 43 Another suggestion was that pneumonia vaccination may prevent COVID‐19 exacerbation due to co‐infections or secondary bacterial infections. 44 , 45 Compared with Streptococcus pneumoniae vaccines, the results of diphtheria, tetanus, and acellular pertussis vaccines should be interpreted with caution because not all sensitivity analyses indicate their corresponding associations as significant. Nevertheless, in support of our results, an in silico study found that combinations of diphtheria, tetanus, and acellular pertussis vaccines induce potential cross‐reactive immunity to SARS‐CoV‐2.…”
Section: Discussionmentioning
confidence: 99%
“… 43 Another suggestion was that pneumonia vaccination may prevent COVID‐19 exacerbation due to co‐infections or secondary bacterial infections. 44 , 45 Compared with Streptococcus pneumoniae vaccines, the results of diphtheria, tetanus, and acellular pertussis vaccines should be interpreted with caution because not all sensitivity analyses indicate their corresponding associations as significant. Nevertheless, in support of our results, an in silico study found that combinations of diphtheria, tetanus, and acellular pertussis vaccines induce potential cross‐reactive immunity to SARS‐CoV‐2.…”
Section: Discussionmentioning
confidence: 99%
“…( 24) Mobility metrics showed a return to near-baseline levels of activity, which could allow the usual avenues of pneumococcal transmission to resume. There is also the possibility of post-SARS-CoV-2 vulnerability to pneumococcal infection, (27) and when ~5% of the population has had a confirmed SARS-CoV-2 infection, this may compromise the baseline health of the population. A further possibility is a mutualistic relationship between IPD and RSV.…”
Section: Discussionmentioning
confidence: 99%
“…The prevalent etiological agents of bacterial pneumonia following antecedent influenza infection (S. aureus, S. pneumoniae, and H. influenzae) are common, persistent, and asymptomatic colonizers of upper respiratory tract [35][36][37][38]. Curiously, this is a trait shared by other microorganisms that are less frequent causes of secondary pneumonia such as S. pyogenes (S. pyogenes) [38,39].…”
Section: Dysregulation Of Innate Immunitymentioning
confidence: 99%
“…In general, susceptibility to bacterial co-infection peaks 6-7 days post influenza infection and corresponds with increases in tissue damage and dysregulation of cytokine production [36,45,46]. In immunocompetent individuals, alveolar macrophages and neutrophils are the primary cell types responsible for controlling bacteria invading the lower respiratory tract (LRT).…”
Section: Dysregulation Of Innate Immunitymentioning
confidence: 99%
See 1 more Smart Citation